Bony Dorsal Preservation - Göksel, Abdulkadir; Tran, Khanh N.; Saadoun, Rakan; Daniel, Rollin K. (Facial Plastic Surgery, 2024)
Rhinoplasty is undergoing a transformation with the reemergence of dorsal preservation rhinoplasty (DPR) techniques. This article introduces a novel addition to the DPR repertoire, “bony dorsal preservation” (BDP), which has particular application for the correction of crooked noses.This comprehensive overview summarizes current DPR concepts and techniques, the intricate considerations that go into the dorsal osseocartilaginous vault and septal management, and how these are modified to treat the crooked nose. However, current DPR techniques, particularly the low septal strip (LSS), have drawbacks, and the desire to address such issues led to the development of BDP.BDP is ideal for cases where there is no septal base pathology. It maintains the core principle of DPR by lowering dorsal humps without creating open roof deformities. Its unique feature is that it temporarily separates the upper lateral cartilages from the septum while leaving the septal base attachment intact, thus allowing the entire osseocartilaginous vault to be adjusted independently before reconnecting the preserved upper lateral cartilages. This technique offers direct visualization during septal excision and fixation and enables cartilaginous vault movement without sacrificing stability. Compared with LSS, there is more septal cartilage available for harvesting, the risks of a single point of septal fixation are eliminated, and there is the potential to transition to component reduction techniques, if needed. With shared indications and contraindications with other DPR methods, BDP emerges as a valuable addition to the evolving field of rhinoplasty, particularly in addressing the challenges of the crooked nose.
Keywords: crooked nose; preservation rhinoplasty; rhinoplasty